Case report: Medical cannabis—warfarin drug-drug interaction - Tyan F. Thomas; Evdokia S. Metaxas; Thu Nguyen; Whitni Bennett; Kathryn V. Skiendzielewski; Diane H. Quinn; Alice L. Scaletta (Journal of Cannabis Research, 2022)
Abstract Aim A case of an 85-year-old patient with concurrent use of warfarin and medical cannabis containing delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) is described. Warfarin continues to be a cornerstone of anticoagulation treatment despite the recent addition of FDA-approved anticoagulant agents. It is well known that warfarin has numerous drug interactions; however, much remains unknown about its interaction with THC and CBD. A literature review was conducted to identify documented cases of possible interactions between cannabis and warfarin. The case reports we identified noted that cannabis may potentially increase warfarin’s effect. Therefore, we aimed to determine why an effect was not seen on our patient’s warfarin dose despite daily use of medical cannabis. Case This case report describes an 85-year-old patient who despite starting an oromucosal medical cannabis regimen of THC and CBD (which provided 0.3 mg of THC and 5.3 mg CBD once daily and an additional 0.625 mg of THC and 0.625 mg CBD once daily as needed) had minimal INR fluctuations from October 2018 to September 2019. Conclusion Despite the introduction and use of medical cannabis therapy, with both THC and CBD components, an elderly patient with concurrent warfarin use did not see major INR fluctuations, in contrast to published literature. The potential for warfarin and THC/CBD interactions may be dependent on route of administration and dose of the cannabis product.